2020
DOI: 10.3390/ijerph17124301
|View full text |Cite
|
Sign up to set email alerts
|

Syndromic Surveillance of Acute Gastroenteritis Using the French Health Insurance Database: Discriminatory Algorithm and Drug Prescription Practices Evaluations

Abstract: The French national public health agency (Santé publique France) has used data from the national health insurance reimbursement system (SNDS) to identify medicalised acute gastroenteritis (mAGE) for more than 10 years. This paper presents the method developed to evaluate this system: performance and characteristics of the discriminatory algorithm, portability in mainland and overseas French departments, and verification of the mAGE database updating process. Pharmacy surveys with certified mAGE from 2012 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The 29 studies identified from the full screen included a range of different syndromic surveillance systems from ten countries and territories across Korea, United States, France, Sweden, Netherlands, Spain, Canada, United Kingdom, Japan, and Portugal. Just over half of the studies (52%, 15/29) were reported from the United States and United Kingdom [8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]. About 55% (16/29) [13,16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] of the studies indicated that syndromic surveillance exhibited the potential to detect GI infections earlier than traditional surveillance, while a further 10% (3/29) of studies indicated that syndromic surveillance exhibits the potential to detect GI infections or symptoms at an early stage but with limitations [15,20,36]; a further 3% (1/29) highlighted that syndromic surveillance exhibits potential to detect GI infections or symptoms at an early stage only when combined with traditional surveillance system [18].…”
Section: Summary Of the Syndromic Surveillance Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 29 studies identified from the full screen included a range of different syndromic surveillance systems from ten countries and territories across Korea, United States, France, Sweden, Netherlands, Spain, Canada, United Kingdom, Japan, and Portugal. Just over half of the studies (52%, 15/29) were reported from the United States and United Kingdom [8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]. About 55% (16/29) [13,16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] of the studies indicated that syndromic surveillance exhibited the potential to detect GI infections earlier than traditional surveillance, while a further 10% (3/29) of studies indicated that syndromic surveillance exhibits the potential to detect GI infections or symptoms at an early stage but with limitations [15,20,36]; a further 3% (1/29) highlighted that syndromic surveillance exhibits potential to detect GI infections or symptoms at an early stage only when combined with traditional surveillance system [18].…”
Section: Summary Of the Syndromic Surveillance Systemsmentioning
confidence: 99%
“…The usefulness of syndromic surveillance in identifying GI infections or symptoms at an early stage was deemed unclear in 24% (7/29) of the included studies [8,12,17,19,21,37,38], while 2/29 of the included studies suggested that syndromic surveillance was incapable of detecting GI infections at an earlier stage in comparison to traditional surveillance [14,39].…”
Section: Summary Of the Syndromic Surveillance Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the WBDO surveillance system, the SNDS is used to identify mAGE cases, defined as follows: any AGE case who consulted a general practitioner and purchased medications prescribed to treat AGE at a pharmacy within 2 days of the consultation. A specific algorithm built in 2011 and regularly updated is used to identify mAGE cases [18,19]. Cases are aggregated according to…”
Section: Health Data Sourcesmentioning
confidence: 99%
“…There is no way for the physician to directly ascertain the compliance of the patient. However, drugs consumption can be inferred from administrative and medical databases, and although the prescription of a drug does not necessarily correspond to the consumption of that drug, it can be considered a good indicator [5,[20][21][22]. It is worth noting that statistical analysis of these kinds of databases is not straightforward because they are commonly characterized by records of tens of thousands of people (or more) for several years.…”
Section: The Importance Of Investigating Drug-switching Behaviorsmentioning
confidence: 99%